2022
DOI: 10.1126/sciimmunol.abj1640
|View full text |Cite
|
Sign up to set email alerts
|

Potent TRIM21 and complement-dependent intracellular antiviral immunity requires the IgG3 hinge

Abstract: Humans have four IgG antibody subclasses that selectively or differentially engage immune effector molecules to protect against infections. Although IgG1 has been studied in detail and is the subclass of most approved antibody therapeutics, increasing evidence indicates that IgG3 is associated with enhanced protection against pathogens. Here, we report that IgG3 has superior capacity to mediate intracellular antiviral immunity compared with the other subclasses due to its uniquely extended and flexible hinge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
(93 reference statements)
2
15
1
Order By: Relevance
“…However, with the main aim of increasing the efficacy of therapeutic mAbs against bacterial targets, many efforts were recently made. Progresses in the field include machine and deep learning approaches for structural prediction (Jumper et al, 2021 ), the design computational design of antibody nanocages (Divine et al, 2021 ), the implementation of mAb immunomodulatory activities through the engineering of the IgG hinge region (Foss et al, 2022 ), the development of nucleic acid-encoded monoclonal antibodies (Schlake et al, 2019 ) and the hetero-oligomerization of therapeutic antibodies (Oostindie et al, 2022 ) ( Figure 1C ). Herein, we discussed novel approaches that show great potential in the fight against AMR.…”
Section: The Future Of Therapeutic Monoclonal Antibodies Against Anti...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, with the main aim of increasing the efficacy of therapeutic mAbs against bacterial targets, many efforts were recently made. Progresses in the field include machine and deep learning approaches for structural prediction (Jumper et al, 2021 ), the design computational design of antibody nanocages (Divine et al, 2021 ), the implementation of mAb immunomodulatory activities through the engineering of the IgG hinge region (Foss et al, 2022 ), the development of nucleic acid-encoded monoclonal antibodies (Schlake et al, 2019 ) and the hetero-oligomerization of therapeutic antibodies (Oostindie et al, 2022 ) ( Figure 1C ). Herein, we discussed novel approaches that show great potential in the fight against AMR.…”
Section: The Future Of Therapeutic Monoclonal Antibodies Against Anti...mentioning
confidence: 99%
“…HINGEneering: Recent studies have demonstrated that the molecular engineering of the hinge region is a valuable tool to modulate the functionality of IgG antibodies (Foss et al, 2022 ; Orr et al, 2022 ). IgG3 is a very potent immunoglobulin, which can trigger different effector functions, including complement activation, antibody-mediated phagocytosis and antibody-mediated cellular toxicity (Damelang et al, 2019 ).…”
Section: The Future Of Therapeutic Monoclonal Antibodies Against Anti...mentioning
confidence: 99%
See 2 more Smart Citations
“… 101 , 102 The latter mechanism would likely be augmented by an IgG antibody response generated from CD11c + /T‐bet + MBCs as they are skewed towards IgG3, as well as IgG1, production. 103 , 104 , 105 IgG3 binds more avidly to cell‐surface FcγRs than other IgG subclasses 106 and also elicits an antiviral response by binding to the intra‐cellular Fc receptor TRIM21, 107 which when bound by immune complexes in DCs, promotes antigen cross‐presentation and stimulation of CD8 + T cells. 108 Furthermore, in murine models of SLE, CD11c + /T‐bet + MBCs cause aberrant differentiation of Tfh cells resulting in impaired affinity maturation of antibody responses.…”
Section: Ebv ‐Induced Activation and Dysfunction Of B Cells ...mentioning
confidence: 99%